1986
DOI: 10.1021/la00067a016
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-liquid equilibria of nonelectrolyte solutions in small capillaries. 1. Experimental determination of equilibrium composition

Abstract: The vapor-liquid equilibrium of an ethanol-water solution held in small pores (pore size range, Aim; median pore size, 13.5 µ ) inside a porous sintered stainless steel plate was determined at 50 °C by using a static method. The vapor pressure of ethanol and of water held in these small pores was found to differ greatly from the values obtained from the Antoine equation. By a treatment of the experimental data, it was shown that the ratio of the vapor pressure of pure ethanol to that of pure water in the capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Furthermore, it is clear that the azeotropic point in this case has shifted from x 1 Х 0.90 to the neighborhood of x 1 → 1. These results are similar to those obtained by Yeh et al (4) and Wong (11). In the case of an ethanol-water system in porous carbon or Teflon plates, however, the change in the VLE is insignificant, with no discernible shift in the azeotropic point.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, it is clear that the azeotropic point in this case has shifted from x 1 Х 0.90 to the neighborhood of x 1 → 1. These results are similar to those obtained by Yeh et al (4) and Wong (11). In the case of an ethanol-water system in porous carbon or Teflon plates, however, the change in the VLE is insignificant, with no discernible shift in the azeotropic point.…”
supporting
confidence: 93%
“…The apparatus has ports for evacuation, pressure measurement, liquid introduction, and sample withdrawal, and upon charging is placed in a thermostatically controlled constant-temperature air bath. A detailed description of the procedure and the still used to study vapor-liquid equilibria in capillary porous plates can be found elsewhere (4,12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Danesh (1998) claimed that the effect of porous media is significant when the pore size is less than 10 nm. Gas can condense (capillary condensation) inside porous media because of the fluid-wall interactions (Yeh et al (1986) and Sigmund et al (1973)). …”
mentioning
confidence: 99%